Village Governance, Community Life, and the 2014 Village Law in Indonesia - Antlöv, Hans; Wetterberg, Anna; Dharmawan, Leni (Taylor and Francis, 2016)
In January 2014, the Government of Indonesia issued Law 6/2014 on Villages, aiming to address weaknesses in the decentralisation paradigm, including providing villages with increased budget allocations and improved governance arrangements. Using longitudinal data from forty Indonesian villages in the three-round Local Level Institution studies, fielded in 1996, 2001 and 2012, the article investigates the effects that prior policy has had on village life and the likely implications of the new Village Law for village governance. The focus is on shifts in capacities, constraints and opportunities for the improved responsiveness of local governments toward community needs. We suggest that there is potential for the Law to increase responsiveness – through a combination of strong financial management systems, new national institutional arrangements, and empowered citizens that can create pressures on the village government to work in the interest of the community – but that substantial risks and obstacles remain.